Is There Income Inequality Convergence Between Regions in Turkey? Panel Data Analysis - Konat, Gökhan (Muş Alparslan Üniversitesi, 2021)
In recent years, with globalization and technological change, it is seen that income inequality has increased in many economies. Therefore, the concept of income inequality is one of the issues that attract attention by researchers. There are many studies on income inequality in the literature. In terms of fiscal policy, the relationship with economic growth is tested, or with financial development. In this study, the validity of the stochastic convergence hypothesis of income inequality is desirable to test for interregional in Turkey. For this purpose, the stationarity test of income inequality was carried out with the panel unit root test. Coefficient of income inequality which expressed as Gini covers the period 2006-2019 and this coefficient to Turkey Statistical Institute has been accessed from the official database. As a result of the panel unit root analysis performed for 12 Regions (Level 1) according to the classification of statistical region units, it was concluded that the Gini coefficient was not stationary. So the hypothesis of convergence between regions in Turkey is not available and there is an imbalance in the distribution of income. Therefore, a lot of work falls on policy makers to ensure justice in income distribution.

Son yıllarda küreselleşme ve teknolojik değişim ile birlikte birçok ekonomide gelir eşitsizliğinin arttığı görülmektedir. Bu yüzden gelir eşitsizliği kavramı araştırmacılar tarafından dikkat çeken konulardan biri olmaktadır. Bu çalışmada Türkiye için bölgeler arası gelir dağılımı eşitsizliğinin stokastik yakınsama hipotezinin geçerliliği sınanmak istenmektedir. Bu amaçla gelir eşitsizliğinin durağanlık sınaması panel birim kök testi ile gerçekleştirilmiştir. Gini katsayısı olarak ifade edilen gelir eşitsizliği serileri 2006-2019 dönemini kapsamaktadır ve bu katsayıya Türkiye İstatistik Kurumu resmi veri tabanından erişilmiştir. İstatistiki bölge birimleri sınıflamasına göre 12 Bölge (Düzey 1) için yapılan panel birim kök analizi neticesinde Gini katsayısının durağan olmadığı sonucuna varılmıştır. Yani Türkiye’de bölgeler arası yakınsama hipotezi geçerli değildir ve gelir dağılımında dengesizlik mevcuttur. Dolayısıyla gelir dağılımında adaleti sağlamak için politika yapıcılara çok iş düşmektedir.
Türkiye’de Bölgeler Arasında Gelir Eşitsizliği Yakınsaması Var Mı? Panel Veri Analizi
anemon
Keywords: Income Distribution Inequality; Convergence; NUTS; Panel Unit Root; Gelir Dağılımı Eşitsizliği; Yakınsama; İBBS; Panel Birim Kök